Aristotle on Notion of Chance and Fortune - Berchmans, Yohanes (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2025)
Aristotle, in his Physics 2.4-9, argued that chance is an accidental cause, which he divided into two types: luck or fortune, which functions in the domain of practice, and the spontaneous, which operates in the natural world. He stated that both luck and the spontaneous are causes by accident and belong to the category of efficient causes. According to Aristotle, chance is considered a cause in the sense that people invoke it to explain what happens not only in the practical realm but also in the natural world. The fundamental question is how chance can be defined within the framework of the four causes. Chance is also rightly described as indefinite, obscure, and uncertain. Aristotle rejected the view held by some that chance is itself a cause - something unclear to the human mind, as if it were divine or a mysterious power. The problem is whether chance and fortune can be seen as causes and considered a fifth cause. This study examines how chance and fortune are neither a substantial reality nor merely a subjective notion; rather, they possess real and meaningful status as accidental causes. They are not additional causes but function within the schema of the four causes, particularly as substitutes in the realm of material explanation.